An empirical assessment of meta-analysis estimates from multi-level studies - Misran, Nurul Afiqah; Nik Idris, Nik Ruzni (2015)
A conventional meta-analysis may be performed using studies which are available at individual patient level (IPD) or aggregate level (AD). Presently however, meta-analysis that combine the two levels of studies is increasingly common. The implications of utilising different levels of data on the overall estimates have not been fully explored. Objective: This study examined the efficacy of the estimates of overall treatment effect from AD, IPD and the mixed AD: IPD studies, and investigated how they differ from the true treatment effect. Additionally, this study investigated the influence of the ratio of AD: IPD on the precision of the overall treatment effects estimates. The bias, root mean-square-error (RMSE) and coverage probability were used to assess the efficiency of the overall estimates. Results: The results showed that the IPD meta-analysis produced better estimates in terms of RMSE compared to AD meta-analysis and the mixed AD:IPD meta-analysis. For the cases where both the AD and IPD studies were available, our findings showed that the combined AD : IPD data produced better estimates, in terms of precision, than utilising the AD alone. Conclusion: It is therefore recommended that available IPD should always be included in a conventional meta-analysis using summary level data as significant